Pelatihan “ACCURATE” sebagai Upaya Peningkatan Profesionalisme Mahasiswa dan Praktisi Akuntansi - Rahmawati Hanny Yustrianthe; Nanik Niandari (LPPM STIKOM Tunas Bangsa, 2022)
This community service activity aims to educate the public regarding accurate accounting aplikasi knowledge and skills. The target of this training is accounting students and practitioners, especially in Yogyakarta and its surroundings. The number of participants is approximately 80 people, and it is carried out online using Zoom Meeting. The training method is divided into several stages: preparation, implementation and evaluation of activities. The expected results of this community service activity are: 1. Participants are able to understand the general description of Accurate Accounting aplikasi applications such as accurate concepts and features. 2. Participants are able to practice accurate aplikasi installation, 3. Participants gain practical experience in doing initial setup and processing transactions both in service/trade companies using accurate applications and discussing problems in using accurate.